Etiology and Treatment Outcome of Neona tal Intestinal Obstruction in a Tertiary Hospital - Islam, SS; Nowshad, MA; Jator, A; Faisal, I; Ahmed, M (TAJ: Journal of Teachers Association, 2009)
A prospective study was conducted on 54 cases of neonatal intestinal obstruction, admitted in Paediatric surgery department of Rajshahi Medical College Hospital during the period from January 2008 to December 2008, a period of 12 months. The objective of the study was to find out etiological aspect and outcome of admitted patient with neonatal intestinal obstruction. The patient constituted 33.7% of total neonatal admission in Paediatric surgery department during the study period. The male: female ratio was 1.4:1 with age ranging from 1 to 28 days. Birth weight of most of the patients was above 2 kg. Most of the patients came from poor and average family. Patients from poor family are slightly ahead. Plain x-ray abdomen was done in all cases in our study. Contrast radiography performed in selected cases. Ultrasound scan done to in selective case to rule out IHPS. No rectal biopsy was taken in case of suspected Hirschsprung's disease. The causes of neonatal intestinal obstruction were in order of frequency-Hirschsprung's disease (45.2%), Intestinal atresia (24.5%), malrotation (9.4%), bands & adhesion (5.6%), meconium ileus (5.6%), volvulus neonatarum (5.6%), meconium plug syndrome (1.8%), unknown (3.7%). 50 patients were treated operatively. 28.3% cases developed complications. Most of the complications were related to colostomy and sepsis. Overall mortality was 20.8%. Mortality was maximum in intestinal atresia. Every patient was advised to come for follow up at the time of discharge but most of the people did not report. In the study only 17 (32.1%) patient came for follow up as per advice. TAJ 2009; 22(1): 198-203